Cover Picture: Fortschritte der Physik 4‐5 / 2016. Issue 4 (April 2016) - Unknown
Abstract : The AdS/CFT correspondence, which holographically relates a gravitational theory in an anti‐de Sitter (AdS) bulk space to a conformally field theory (CFT) on the AdS boundary, has led to many deep and new insights about the structure of gauge theories and about questions in quantum gravity and black holes. The cover picture of this year is showing a projection of an AdS space with a black hole in its interior. (Image on title page by Migael Strydom and Johanna Erdmenger)